The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1007/bf00316825
|View full text |Cite
|
Sign up to set email alerts
|

Human parathyroid blood supply determined by laser‐Doppler flowmetry

Abstract: The blood supply of 53 normal human parathyroid glands was studied with laser Doppler flowmetry in 45 patients undergoing operations on the thyroid and parathyroid glands. The inferior and superior thyroid arteries and other vessels that might supply the parathyroid glands were occluded so their contribution to parathyroid perfusion could be studied. Occlusion of the main trunk of the inferior thyroid artery resulted in a reduction of blood flow by one-third, and a similar reduction was obtained after occlusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0
5

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 12 publications
4
15
0
5
Order By: Relevance
“…They also demonstrated the occurrence of two or more feeding arteries in one-third of the parathyroid glands. These findings are not concordant with earlier anatomic studies, which demonstrated that the glands were supplied by a single artery mostly arising from the inferior thyroid artery [5,6], but they are in accordance with our functional studies of the vascular supply in normal parathyroid glands [13].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…They also demonstrated the occurrence of two or more feeding arteries in one-third of the parathyroid glands. These findings are not concordant with earlier anatomic studies, which demonstrated that the glands were supplied by a single artery mostly arising from the inferior thyroid artery [5,6], but they are in accordance with our functional studies of the vascular supply in normal parathyroid glands [13].…”
Section: Discussionsupporting
confidence: 73%
“…Functional studies of parathyroid blood supply have been possible, and an earlier study demonstrated a variable arterial blood supply to normal parathyroid glands [13]. The variability of LDF in repetitive recordings in normal and pathologic glands is not known.…”
mentioning
confidence: 99%
“…Curtis reported the presence of anastomoses between parathyroid arteries and thyroid glandular tissue, which were spared after subtotal thyroidectomy [26]. Furthermore, several other studies reported that parathyroid vascularization may also be compensated through anastomotic circuits via peritracheal and/or periesophageal arteries [27][28][29]. Hence, no significant difference in term of postoperative hypocalcemia have been observed after subtotal thyroidectomy between patients undergoing ITA truncal ligature and those undergoing terminal branch ITA ligature [9,12].…”
Section: Discussionmentioning
confidence: 97%
“…As a prerequisite to improve the standard of care, various unresolved questions have to be answered concerning the number [6,18,19], blood supply [20,21] and discolouration of parathyroid glands [22,23]. Furthermore the effectiveness of autotransplantation is discussed controversially in literature [9,[24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%